Preparing and training for CPR. Issue 2 (28th February 2019) - Mathis, Alessandra
Abstract : With veterinary medicine offering ever higher levels of care, allowing sicker patients to be treated, witnessing cardiopulmonary arrest is not uncommon in practice and veterinary practitioners and their support staff should be ready to perform cardiopulmonary resuscitation (CPR). However, while hands‐on training in veterinary CPR techniques is increasingly available, less emphasis has been placed on the importance of preparation at a practice level so that CPR can be initiated without delay. This article discusses some of these practical preparations and the importance of training the veterinary team to deliver effective CPR if needed.